Financial participation of employees in the European Union: much ado about nothing? Background paper - Welz, Christian; Fernández Macías, Enrique (Dublin, 2007)
"The research indicates that financial participation can deliver real benefits for employees, enterprises and national economies. However, despite this potential, it remains little used in most Member States, and is very unevenly distributed across the EU. This background paper has updated the Foundation’s research on financial participation using employee data for the first time, from the fourth European Working Conditions Survey (EWCS)."